2021
DOI: 10.1016/j.injury.2020.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of geriatric trauma patients in Norway: A nationwide analysis of Norwegian Trauma Registry data, 2015–2018. A retrospective cohort study

Abstract: Introduction: Geriatric patients have a high risk of poor outcomes after trauma and is a rapid-increasing group within the trauma population. Given the need to ensure that the trauma system is targeted, efficient, accessible, safe and responsive to all age groups the aim of the present study was to explore the epidemiology and characteristics of the Norwegian geriatric trauma population and assess differences between age groups within a national trauma system. Materials and methods:This retrospective analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 42 publications
5
19
0
2
Order By: Relevance
“…Large numbers of studies have also reported increasing numbers of falls and especially in patients aged ≥ 65. (10)(11)(12)30) In UK, the proportion of fall injuries < 2 m among severely injured patients increased from 4.7% from 1990 to 39.1% in 2013. (12) Ten-year trends from 2005-2014 in a statewide trauma registry in Oklahoma, USA, found the APC of fall injuries to increase by 4.0% (95% CI: 3.1-4.9%) and the number of fall injuries among patients ≥ 65 more than doubled.…”
Section: Mechanism Of Injurymentioning
confidence: 99%
“…Large numbers of studies have also reported increasing numbers of falls and especially in patients aged ≥ 65. (10)(11)(12)30) In UK, the proportion of fall injuries < 2 m among severely injured patients increased from 4.7% from 1990 to 39.1% in 2013. (12) Ten-year trends from 2005-2014 in a statewide trauma registry in Oklahoma, USA, found the APC of fall injuries to increase by 4.0% (95% CI: 3.1-4.9%) and the number of fall injuries among patients ≥ 65 more than doubled.…”
Section: Mechanism Of Injurymentioning
confidence: 99%
“…Pre‐existing medical conditions such as diabetes mellitus, obesity, heart disease and hypertension are more frequent and contribute to morbidity in elderly trauma patients 19 . In Norway, Cuecas‐Østrem et al studied geriatric trauma patients nationwide from 2015 to 2018 20 . They included adult trauma patients with a New Injury Severity Score (NISS) ≥ 9 and older than 16 years and compared them to patients aged ≥65.…”
Section: Discussionmentioning
confidence: 99%
“…We found a decreasing APC in pedestrian injuries of −4.7% and scooter injuries of −6.0%. Many studies have also reported increasing numbers of falls, especially in patients aged ≥65 10–12,20 . In the UK, the proportion of fall injuries <2 m among severely injured patients increased from 4.7% in 1990 to 39.1% in 2013 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations